PENGARUH TANGGUNGJAWAB SOSIAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Eindye Taufiq; Widayatmoko Widayatmoko (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
This study aims to examine the application of corporate social responsibility and financial performance to firm value. The population of this research is mining companies listed on the Indonesia Stock Exchange. For analysis using SPSS software. The results of the study found that the application of corporate social responsibility does not affect firm value. Financial performance affects firm value because the company is still focused on achieving efforts to generate profits economically. The findings of this study suggest that determining the value of the company in the eyes of stakeholders is not only seen from the financial aspect but also has to look at the extent to which the company's social and environmental obligations are fulfilled. Companies must seriously implement corporate social responsibility as a company advantage to create added value in the eyes of investors. The government must formulate tax policies that can improve the implementation of corporate CSR.